Optimization of a structured illumination spectrophotometric technique for optical properties determination of dense solutions - Thomas Koffi; Guy-Oscar Regnima; Emmanuel Gozoua; Mensah Edoe; Serge Adepo; Evariste Amany; Jocelyne Bosson; Jérémie Zoueu (Scientific African)
The Structured Laser Illumination Planar Imaging (SLIPI) technique is an alternative approach to the limitations of classical absorption spectrophotometry techniques for the diagnosis of optically dense solutions. In this study, the performance of the single-phase configuration of these optical device 1p-SLIPI, was tested over a wide range of levels of coffee’s concentrations. The lock-in detection algorithm developed from Fourier transform of raw images, allowed to effectively remove the contribution of multiple scattering in these images. Thus, ballistic photons and those of single scattering accounting for the effective absorption of the probed media are selected. These photons were therefore used to accurately assess optical properties of our samples. The results are impressive, establishing a significant area of ​​reliability for the measurements carried out: coffee solutions with concentrations between 3.79 g/L and 20.21 g/L, probed with cw diode lasers of wavelengths 450 nm and 638 nm. This allows to classify samples according to the concentration level, by evaluating the extinction coefficients. This study clearly shows that the SLIPI technique could be a good alternative to the limits of the classical Beer-Lambert absorptivity law for dense and diffusing solutions.